Demonstration of toxicity to fish and to mammalian cells by Pfiesteria species: Comparison of assay methods and strains - Burkholder, JoAnn M. (Proc Natl Acad Sci U S A, 2005)
Toxicity and its detection in the dinoflagellate fish predators Pfiesteria piscicida and Pfiesteria shumwayae depend on the strain and the use of reliable assays. Two assays, standardized fish bioassays (SFBs) with juvenile fish and fish microassays (FMAs) with larval fish, were compared for their utility to detect toxic Pfiesteria. The comparison included strains with confirmed toxicity, negative controls (noninducible Pfiesteria strains and a related nontoxic cryptoperidiniopsoid dinoflagellate), and P. shumwayae strain CCMP2089, which previously had been reported as nontoxic. SFBs, standardized by using toxic Pfiesteria (coupled with tests confirming Pfiesteria toxin) and conditions conducive to toxicity expression, reliably detected actively toxic Pfiesteria, but FMAs did not. Pfiesteria toxin was found in fish- and algae-fed clonal Pfiesteria cultures, including CCMP2089, but not in controls. In contrast, noninducible Pfiesteria and cryptoperidiniopsoids caused no juvenile fish mortality in SFBs even at high densities, and low larval fish mortality by physical attack in FMAs. Filtrate from toxic strains of Pfiesteria spp. in bacteria-free media was cytotoxic. Toxicity was enhanced by bacteria and other prey, especially live fish. Purified Pfiesteria toxin extract adversely affected mammalian cells as well as fish, and it caused fish death at environmentally relevant cell densities. These data show the importance of testing multiple strains when assessing the potential for toxicity at the genus or species level, using appropriate culturing techniques and assays.